Eksplorasi Persepsi Pelaku UMKM dan Pemahaman Akuntansi Terhadap Intensi Penggunaan SAK EMKM pada UMKM Bidang Perdagangan di Kota Denpasar - Ketut Tanti Kustina; Ni Putu Linda Arya Pratiwi (Universitas Matana, 2022)
This study aims to 1) find out the effect of the variable perception of MSME actors on the intention to use SAK EMKM on MSMEs in the trade sector in Denpasar City and 2) find out the influence of the variable understanding of accounting on the intention to use SAK EMKM on MSMEs in the trade sector in Denpasar City. The research population is 11,126 business units. The research sample using the solvin formula resulted in 100 respondents who were SMEs in the trade sector in Denpasar City. The data was processed by multiple linear regression analysis. The results of the study suggest, 1) the perception variable of MSME actors has a positive and significant influence on the intention to use SAK EMKM in MSMEs in the trade sector in Denpasar City. 2) the variable of accounting understanding has a positive and significant influence on the intention to use SAK EMKM in MSMEs in the trade sector in Denpasar City. Keywords: Perception of MSME Actors, Accounting Understanding, Intention of Use, SAK EMKM